TRANSFER PRICING DAN PROFITABILITAS: STRATEGI TERSEMBUNYI DIBALIK PENGHINDARAN PAJAK DI INDONESIA - Stefani Darmawan; Rimi Gusliana Mais (Juremi: Jurnal Riset Ekonomi, 2025)
This study analyze the influence of transfer pricing implementation and profitability on tax avoidance practices conducted by multinational companies in Indonesia. Using a qualitative descriptive analytical approach, this research involved finance directors, tax managers, Directorate General of Taxation officials, and tax consultants as informants. Data were collected through in-depth interviews, observations, and documentation analysis over eight months in Jakarta, Surabaya, and Medan. Results indicate that 85% of multinational companies utilize transfer pricing schemes as global tax optimization instruments through comparable uncontrolled price and transactional net margin methods. Companies with high profitability levels (ROA >15%, ROE >20%, profit margin >25%) demonstrate more aggressive tendencies toward tax avoidance through transfer price manipulation, excessive management fees, and intercompany financing. These practices result in potential tax revenue losses of 25-40% from total corporate income tax that should be paid. The effectiveness of Indonesia's transfer pricing regulations remains suboptimal due to limited human resources and multinational transaction complexity. The study recommends strengthening DGT human resource capacity, improving regulatory frameworks, developing integrated information systems, and enhancing international collaboration to increase transfer pricing supervision effectiveness in Indonesia.